A Feasibility study natural dyeing facility - Canusa, Riezl Myreen; Marquez, Michael; Melivo, Allan; Zarzuela, Rosario Cinderela (College of Engineering, 1997)
In line with the Katutubong Filipino Foundation's goal to extend and improve the livelihood of local indigenous communities and to revive local dyeing practices, the KFF has decided to investigate the feasibility of putting up a natural dyeing facility. With the help of the Philippine Textile Research Institute. First, the team determined the magnitude of the demand for natural dyes and for its service facility. The group went about collecting data by first consulting with published forms of data, such as journals, reports, and other literature pertaining to natural dyes and the garments and textile industry. Then, the group consulted with PTRI, Garments and Textile Export Board (GTEB), One-Earth Philippines and the KFF. The group then released a survey to local designers, couturiers and garment exporters concerning their use with natural dyes. Follow-up interviews with certain individuals such as Mr. Ricky Lo, Ms. Edna Fernandez, and Menchu Versoza. From the data gathered, marketing strategies and plans were designed such that the natural dyes and its service facility will reach and be accepted by its target users. The total demand for natural dyeing is correlated to the number of pieces of high-end products has been continually increasing since 1989, thus the market opportunity for establishing a natural dyeing facility exists. Currently, there are no commercial natural dyeing facilities in the Philippines but there is ample competition from natural dyeing facilities abroad. The group analyzed the proposed natural dyeing facility can meet this foreign competition head-on by counting on its competitive advantage in two major areas: lead time and freight costs. From the market study conducted by the group, the analysis is made indicated that 7.92% to 11.24% of the demand for natural dyeing can be serviced by the facility. An annual marketing budget of P 57,305.00 can also be expected for the first six to seven years to cover the costs for promoting the service. Being assured of the feasibility of its market, the team determined whether the production of natural dyes and setting-up of a natural dyeing facility is technically feasible. For the technical study, the group determined dye source requirements, chemical requirements, water requirements, number of machines, number of workers, production and office space requirements to meet the demand. Evaluating the proposed size, location and production process, it was found that the magnitude and capacity of the proposed facility could satisfy a certain portion of the actual demand of natural dyeing in the Philippines with the facility running at a single shift, eight hours a day and six days a week. Being located at Penarrubia, Abra, the facility would have easy access to raw material suppliers and skilled labor. Engineering features input resources and sustained production were also favorable for the proposed facility. From the technical study, the total project cost was computed to be P 4,141,285.28. A financial study was conducted to determine if the proposed facility would be operating profitably. This is to determined whether the facility is capable of generating cash, generating return made on financiers investments, gives its creditors ample protection and if its capable of servicing debts. On all points the project was evaluated to be financially feasible with a net present value of P 729,284.02, an internal rate of return of 31.79% and a payback period of 4.7. The group conducted an organizational and management study to provide an organization for the facility. The natural dyeing facility will operate as a corporation with the Katutubong Filipino Foundation (KFF) as the major shareholder. The Board of Directors will be comprised of duly elected Katutubong Filipino Foundation members, and that financing will be received from KFF members and organization holdings. The facility will be employing a plant manager, a production supervisor, a purchasing assistant, a secretary/bookkeeper, an accountant on a retainer basis, production workers and a security guard. Production workers vary every year to meet the demand for natural dyeing. For the first year, the facility will consist of ten personnel. Vastly, the group conducted a social profitability study to determine the socio-economic contributions that the project can offer and to determine whether the establishment of the facility is socially attractive and not based on mandated criterion. The establishment of the natural dyeing facility in Penarrubia, Abra will generate employment by utilizing the skills of local plant farmers and also generate an alternative means of income for families. The project would make available for the first time a natural dyeing facility, which can serve the local market who still have their fabrics dyed abroad. Capturing this market will generate foreign exchange savings, because, now, this market will not have to pay in foreign currencies. There would be utilization of local materials resulting from the demand of the facility for natural dye plant resources. Currently, the plants needed by the facility are being mass grown in Abra but do not serve as industrial input to any production. In terms of taxes from which the local government can benefit from and could be used for community development, the project will not directly contribute to the government coffers because it is a pioneering industry and is exempted from the income taxes for the first five years. The indirect taxes it would generate will come from the individuals and families whose incomes are increased because of supplying plants for the facility.